ANALISIS PENDAPATAN PETANI MITRA DAN NON MITRA PADA PT. SIRTANIO ORGANIK INDONESIA DI KABUPATEN BANYUWANGI - Fakhruddin Yulistiono; Triana Dewi Hapsari (UNEJ e-Proceeding, 2018)
Banyuwangi Regency is a district that implements organic farming, there are two institutions engaged in organic agriculture that have been certified by LeSOS in Banyuwangi Regency, namely PT. Sirtanio Organik Indonesia and Sumber Urip Farmers Group. Farmer's reason for joining PT. Sirtanio Organik Indonesia is one of them to increase income. This study aims to determine the difference in income between farmer partners and non-partners of PT. Sirtanio Organik Indonesia. Sampling method to determine the income of partner and non-partner farmers PT. Sirtanio Organic Indonesia is using total sampling. Data collection methods used in this study use interviews, observation and literature studies. The analytical method used is analytic. The results showed that there were significant differences between the income of partner and non-partner farmers. The average cost incurred by partner farmers is Rp. 9,790,724 / Ha while the costs incurred by non-partner farmers amounted to Rp. 12,904,945 / Ha. The average partner farmer acceptance is Rp. 28,160,273 / Ha, the average income of non-partner farmers is Rp. 27,761,520 / Ha. Partner farmer income of Rp. 18,369,549 / Ha, while the income of non-partner farmers is Rp. 14,856,575 / Ha.